ADOÇÃO DO MANEJO INTEGRADO DE PRAGAS BASEADO NA PERCEPÇÃO E EDUCAÇÃO AMBIENTAL - Carvalho, Nathália Leal; Barcellos, Afonso Lopes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704204 Complete extermination of the pests!This was the goal of applied entomology from 40 years.Although believed to be radical in its feasibility with the development of new insecticides such asDDT and BHC, cheap, broad-spectrum that any consideration of the economic order wasirrelevant. Over time, the indiscriminate use of pesticides has caused serious disruptions in theenvironment such as the selection of resistant individuals, the resurgence of species controlled,pest outbreaks of secondary importance, shrinking populations of beneficial insects, harmful effects on wildlife and domesticated animals, including man, and the accumulation of toxicresidues in soil, water and food. Because of these problems we develop the theory of biologicalcontrol with predators, parasites and methods of population control and the maintenance conceptof insects in economically tolerable levels, through ecosystem management, based on increasedknowledge of applied ecology and population dynamics. These two approaches, seemingly distantfrom each other, have common point in the perception that predators and parasites can onlysurvive if the prey also survive. Forged, therefore, a concept based on the awareness andenvironmental concern, which gave the name of integrated control. This control should not beseen as the juxtaposition of two control techniques (such as chemical and biological controls) but,as the integration of appropriate management techniques. Thus, failures in some chemicaleradication programs, an economic and a social-ecological awareness have led to the integratedcontrol approach was accepted. Currently the concern about the harmful effects to non-targetorganisms and the environment, a more comprehensive philosophy, called integrated pestmanagement - IPM began to be perceived and felt, and is gaining more adherents in order toproduce an environmentally friendly and sustainable.